2022
DOI: 10.3390/educsci12020134
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effects of Physical Activity on Specific Academic Skills of School Students

Abstract: This systematic review examined the effects of distinct physical activity interventions on the academic achievement of school students based on an analysis of four distinct outcomes: mathematics, language, reading, and composite scores. This study was performed in accordance with the PRISMA guidelines and the QUORUM statement. A literature search was conducted using the PubMed-MEDLINE, Scopus, and Web of Science databases. Peer-reviewed studies published in English, Portuguese, and Spanish were considered. A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…A study conducted by Troiano's [59] team indicated that 42% of children aged 6-11 years in America met the recommended 60 min per day PA norm, whereas only 8% of adolescents reached this norm, and similar data were found in Australia [60]. Much research has estimated that students' decline in physical activity during the pandemic period was negatively associated with a lack of psychological wellbeing, depression, and sadness [49,61,62], which can indirectly lead to reduced academic performance [63,64].…”
Section: Discussionmentioning
confidence: 86%
“…A study conducted by Troiano's [59] team indicated that 42% of children aged 6-11 years in America met the recommended 60 min per day PA norm, whereas only 8% of adolescents reached this norm, and similar data were found in Australia [60]. Much research has estimated that students' decline in physical activity during the pandemic period was negatively associated with a lack of psychological wellbeing, depression, and sadness [49,61,62], which can indirectly lead to reduced academic performance [63,64].…”
Section: Discussionmentioning
confidence: 86%
“…The duration of the interventions ranged from one day [12] to five years [52], with 25 studies [8,[10][11][12]17,[19][20][21][26][27][28]32,[34][35][36]38,40,42,43,53,54,57,59,60,62] lasting less than one year. Post-intervention follow-ups, conveyed in 26 research articles [9,11,13,15,17,19,20,23,[26][27][28]31,35,36,37,40,42,43,[51][52][53][54][55]57,[...…”
Section: Resultsmentioning
confidence: 99%
“…Regarding intervention types, 13 studies involved extensive multi-component strategies [ 8 - 16 , 31 , 34 , 52 , 55 ], 15 were nutrition education interventions [ 17 , 19 , 20 , 21 , 23 - 27 , 51 , 57 , 59 - 62 ], six focused on physical activity interventions [ 28 , 32 , 35 , 36 , 38 , 54 ], and four on lifestyle and nutrition-related behavior [ 40 , 42 , 43 , 53 ]. Another 24 of the 62 included studies [ 1 - 7 , 18 , 22 , 26 , 29 , 30 , 33 , 37 , 39 , 41 , 44 - 50 , 58 ] were original articles, review articles, and government guidelines, protocols, policies, and reports regarding school children and adolescents’ nutritional status.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to fundamental motor skills, another aspect of motor function that has received extensive focus is physical activity (PA). Recent meta-analyses and systematic reviews have confirmed the general link between PA and cognitive abilities in children [37][38][39][40], but as in the motor skills/cognition research, consensus has not yet been established regarding which types of PA exert beneficial effects on which particular cognitive functions [41]. For example, Egger et al [42] conducted a classroom-based intervention study with 142 7-to 9-year-old children.…”
Section: Introductionmentioning
confidence: 99%